Comparison of growth and reproductive performance of exotic, indigenous and cross breeds of pigs in Nepal - Shashi Sharma, Chiranjibi Pantha , Prakash Kumar Yadav , Suman Karki; Nabaraj Poudel (African Journal of Pig Farming, 2019)
The objective of this study is to evaluate growth and reproductive performance of the exotic, indigenous and cross breeds of pigs in Nepal. A total of 42 female piglets were selected, 7 each from breed in Hampshire, Pakhribas black, Nagpuri, Hurrah, Pakhribas black X Nagpuri and Hampshire X Hurrah; and are kept under 6 treatments with 7 replications. Mean body weight, age at first mating, litter size at weaning, litter weight at weaning and farrowing interval were significant (p<0.05%). Weight at first mating and litter index sow/year were significant (p<0.01). Age of first farrowing, litter size at birth, weight of piglets at birth and piglet mortality % were non significant. Exotic breed Hampshire has the highest adult body weight than synthetic breed Pakhribas followed by cross breed Pakhribas X Nagpuri, Hampshire X Hurrah and local breeds Nagpuri and Hurrah. Age at first mating, age at first farrowing and piglet mortality % were higher in local breeds. Litter size at birth, litter size at weaning and weight of piglets at birth were higher in Pakhribas. Weight at first mating and litter weight at weaning were higher in exotic breed. Farrowing interval was higher in local breed. Litter index was higher in synthetic and exotic breeds.